Comparison between primary school children of urban and rural areas for prevalence of uncorrected refractive errors and amblyopia - Singh, Priti; Agarwal, Rahul; Kashiv, Yuri; Gupta, S B; Kumar, Rashmi (International Journal of Medical Research and Review, 2015)
Aims: The present study was planned to evaluate the prevalence of uncorrected refractive errors and the frequency of amblyopia in primary school children, and to compare the findings between rural and urban settings. Material and Method: It was a cross sectional study in which 560 children studying in 1st to 6th standard in age group of 6 to 10 years in primary school of urban and rural area were evaluated for uncorrected refractive errors and amblyopia. All children underwent a preliminalary examination at school level and those who were having refractive errors were further undergone a detail eye check up at ophthalmology OPD of our medical college. Later on the data was analysed statistically. Results: The prevalence of uncorrected refractive errors was found to be 10.35% (29/280) in urban area and 8.57% (24/280) in rural area. Out of total uncorrected refractive errors, mostly have uncorrected myopia both in urban and rural areas. Conclusion: Difference in prevalence of uncorrected refractive errors and amblyopia was found to be statistically insignificant in both the urban and rural primary school children. (p value=0.564 for uncorrected refractive errors and p value=1 for amblyopia)